The Shrinking Foreign Market for United States Cotton - White, Bennett S. (Quarterly Journal of Economics, 1940)
Introduction, 255.— Foreign consumption of American and other cottons, 256.— Factors affecting foreign mill consumption: industrial production and the demand for textiles, 256; substitute fibers, 259; other factors, 261.— Factors affecting the kind of cotton consumed: development of manufacturing in new areas, 263; trade regulations, 265; substitute fibers, 267; changes in relative supplies, 267. Factors responsible for the change in relative supplies: agricultural and commercial policies of the United States, 269; prices for cotton and competing crops in foreign countries, 271; currency depreciation, 272; crop restriction and price-pegging, 272.— The situation summarized, 274.